2009
DOI: 10.1007/s12640-009-9044-y
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein Treatment Attenuates Microglial Activation and Expression of Neurotoxic Quinolinic Acid Following Traumatic Brain Injury

Abstract: The kynurenine pathway has been implicated as a major component of the neuroinflammatory response to brain injury and neurodegeneration. We found that the neurotoxic kynurenine pathway intermediate quinolinic acid (QUIN) is rapidly expressed, within 24 h, by reactive microglia following traumatic injury to the rodent neocortex. Furthermore, administration of the astrocytic protein metallothionein attenuated this neuroinflammatory response by reducing microglial activation (by approximately 30%) and QUIN expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Moreover, the results are generally consistent with those found in Mt1&2 KO mice [12]. An inhibitory effect of MT-1/2 on microglia has also been suggested in other studies [25,26,27]. Altogether, the present results suggest that while MT-1 may have a direct inhibitory role controlling microglia, it is overridden by an indirect stimulatory role in the case of APP positive mice because of its effects on the formation of amyloid plaques.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the results are generally consistent with those found in Mt1&2 KO mice [12]. An inhibitory effect of MT-1/2 on microglia has also been suggested in other studies [25,26,27]. Altogether, the present results suggest that while MT-1 may have a direct inhibitory role controlling microglia, it is overridden by an indirect stimulatory role in the case of APP positive mice because of its effects on the formation of amyloid plaques.…”
Section: Discussionsupporting
confidence: 89%
“…Neuroinflammation has been linked to alpha-synucleinopathies and there is evidence of a role of MTs in inflammation in brain injury (Chung et al, 2009; Pedersen et al, 2009; Shastri et al, 2013; Vieira et al, 2015). MTs have been implicated in inflammatory states and act as exchangeable zinc stores which can swap with toxic metals, such as copper and cadmium (Rofe et al, 1992; Meloni et al, 2008).…”
Section: Oxidative Stress and Neuroinflammationmentioning
confidence: 99%
“…Astrocytes, the primary cell type expressing MT-1/2 in the brain, up-regulate MT-1/2 expression as a physiological response which may promote neuroregeneration as well as survival (Chung et al, 2008; Landowski et al, 2016). Treatment with MT-2 attenuated the immune response of neurotoxic quinolinic acid production in brain injury (Chung et al, 2009). More recently, overexpression of MT-1 in a mouse model of AD promoted reversal in behavioral symptoms of disease and more inert soluble amyloid species (Manso et al, 2016).…”
Section: Oxidative Stress and Neuroinflammationmentioning
confidence: 99%
“…Similarly, extracellular MT reduces the inflammatory response of microglia following activation (Chung et al 2009). These findings complement earlier work by Lynes’ group, which showed that MT was able to act in a chemokine-like manner and to influence the migration of leukocytes (Yin et al 2005).…”
Section: Endogenous Neuroprotective Molecules (Akw Gjg)mentioning
confidence: 99%